Phytochemical Screening, Antioxidant and Antidiabetic Activities of Extracts of Leaves and Seeds of Carica papaya - Pokhrel, Shanta; Karki, Puja (Nepal Journal of Science and Technology, 2021)
The phytochemicals, phenolic, flavonoid contents, and antibacterial, antioxidant and antidiabetic activities of leaves and seeds extract of Carica papaya via Soxhlet extraction were investigated. The phytochemical screening indicated different bioactive compounds such as saponins, alkaloids, glycosides, tannins, polyphenols, steroids, and flavonoids in different extracts. The total phenolic content (TPC) was determined spectrophotometrically by Folin–Ciocalteu reagent method and aluminium chloride reagent to measure total flavonoid content (TFC). TPC was found more in leaf methanol extract (LME) (93.18±0.40 mg GAE/g) than that in seed methanol extract (SME) (89.14±0.45 mg GAE/g). Comparatively, the flavonoid content was found more in LME (18.85±0.061 mgQE/g) than in SME (16.64±0.065 mgQE/g). The antioxidant activity was assessed for LME and SME by DPPH radical scavenging activity and IC50 values. The IC50 values of LME and SME were 43.54±0.007 and 15.48±0.13µg/mL, respectively. Thus, seeds methanol extract showed better antioxidant activity than leaves methanol extract. The antidiabetic assay was performed via α- amylase inhibition method. Among the selected parts (seeds and leaves), methanol seed extract exhibited high α-amylase inhibition with an IC50 value of 46.99±0.018 µg/mL. The study explored the potential value of Carica papaya in medicinal applications.